Microbial metal‐sulfide oxidation in inactive hydrothermal vent chimneys suggested by metagenomic and metaproteomic analyses. (21st January 2019) - Meier, Dimitri V.; Pjevac, Petra; Bach, Wolfgang; Markert, Stephanie; Schweder, Thomas; Jamieson, John; Petersen, Sven; Amann, Rudolf; Meyerdierks, Anke
Summary: Metal‐sulfides are wide‐spread in marine benthic habitats. At deep‐sea hydrothermal vents, they occur as massive sulfide chimneys formed by mineral precipitation upon mixing of reduced vent fluids with cold oxygenated sea water. Although microorganisms inhabiting actively venting chimneys and utilizing compounds supplied by the venting fluids are well studied, only little is known about microorganisms inhabiting inactive chimneys. In this study, we combined 16S rRNA gene‐based community profiling of sulfide chimneys from the Manus Basin (SW Pacific) with radiometric dating, metagenome ( n = 4) and metaproteome ( n = 1) analyses. Our results shed light on potential lifestyles of yet poorly characterized bacterial clades colonizing inactive chimneys. These include sulfate‐reducing Nitrospirae and sulfide‐oxidizing Gammaproteobacteria dominating most of the inactive chimney communities. Our phylogenetic analysis attributed the gammaproteobacterial clades to the recently described Woeseiaceae family and the SSr‐clade found in marine sediments around the world. Metaproteomic data identified these Gammaproteobacteria as autotrophic sulfide‐oxidizers potentially facilitating metal‐sulfide dissolution via extracellular electron transfer. Considering the wide distribution of these gammaproteobacterial clades in marine environments such as hydrothermal vents and sediments, microbially accelerated neutrophilic mineral oxidation might be a globally relevant process in benthic element cycling and a considerable energy source for carbon fixation in marine benthic habitats.